The ideal of «Spanish Music» in Enlightenment Zarzuelas - Germán LABRADOR LÓPEZ DE AZCONA (Cuadernos Dieciochistas)
Despite the novelty and even the reformist drive in the birth of zarzuela nueva in the mid 1760s, both the music and libretti of the new genre were alien to the «national tradition». In fact, the origins of the «zarzuela nueva» do not lie here, but rather in the opera bufa, a new and attractive genre for the Spanish public, although these operas was shortened and some parts were omitted (for instance, the recitativos). Considering the development of the zarzuela «nueva» or «jocosa», there seem to have been no reasons to promote truly popular works, or with truly national music, but rather the contrary. The zarzuela of the Enlightenment time did not favour «castiza» or «national» music, and even in the few works which included rhythms and dances based on the national tradition these would later be replaced by arias, recitativos and fashionable dances of foreign origin. The contrary also happened, and jácaras or seguidillas were inserted in zarzuelas with music by Piccinni or Pergolesi. Thus, the «zarzuela nueva» is shaped as a hybrid genre, were opera bufa elements are integrated with others from Spanish national tradition.